WORK-LIFE BALANCE OF WOMEN ENTREPRENEURS IN THE TEXTILE SECTOR IN KANYAKUMARI DISTRICT - Sajima, S. Metlin; T. P. Sherin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Work-life balance is essential for women entrepreneurs to sustain their business success while nurturing their personal lives. The purpose of this study is to highlight the work-life balance challenges women entrepreneurs encounter in the textile sector. Moreover, this research aims to examine whether work-life imbalance affects women entrepreneurs’ career growth in the textile sector in Kanyakumari district. The primary data of this study were collected from fifty women entrepreneurs in the textile sector. The statistical tools used to analyse the data were percentage analysis, chi-square test of independence and weighted average ranking method. The statistical analysis was done using Jamovi v2.6.44 and MS Excel. The findings of the study revealed that most of the respondents believe that work-life imbalance affects their career growth. Another key insight is that stress was found to be the major problem faced by women entrepreneurs in work-life balance. Eventually, this research provides suggestions that will assist women entrepreneurs in enhancing their work-life balance.